USING A “PROSING POEM” STRATEGY IN TEACHING POETRY IN THE EFL CONTEXT OF INDONESIA - Amri, M Misbahul; Basthomi, Yazid (TEFLIN Journal, 2022)
The present article reports our reflections on how to teach an introductory course on poetry in an Indonesian tertiary educational institution where English is a foreign language. The reflections are made on the basis of our experiences of teaching the course, the main challenge of which centres on students’ wronged perception of what poetry is; students tend to have an entrenched idea that poetry must be perplexing. The reflections have led us to a teaching strategy which we call “prosing poem.” Applying the strategy, we help students by providing made-up prosaic forms of the poems. This strategy has proven to help demystify students’ idea on poetry as a difficult subject. It allows students to unpack the poetic texts in a less daunting way as they can rely on their English mastery without having cognitive block.